Predicting the Remaining Lifespan and Cultivation-Related Loss of Osteogenic Capacity of Bone Marrow Multipotential Stromal Cells Applicable across a Broad Donor Age Range - Sarah M. Churchman; Sally A. Boxall; Dennis McGonagle; Elena A. Jones (Stem Cells International)
Background and Objectives. Culture expanded multipotential stromal cells (MSCs) have considerable potential for bone regeneration therapy but their wider use is constrained by the lack of simple and predictive assays of functional potency. Extended passaging leads to loss of multipotency but speed of decline depends on MSC donor age. The aim of this study was to develop an assay predictive of MSC culture longevity applicable to a broad donor age range. Materials and Methods. Bone marrow (BM, n=7) was obtained from a diverse range (2–72 years) of healthy donors. MSCs were culture expanded to senescence and their osteoprogenitor content, gene expression profiles, epigenetic signature, and telomere behaviour were measured throughout. Output data was combined for modelling purposes. Results. Regardless of donor age, cultures’ osteoprogenitor content correlated better with remaining lifespan (population doublings before senescence, PD-BS) than proliferative history (accrued PDs). Individual gene’s expression or telomere length did not predict PD-BS but methylation of individual CpG islands did, PRAMEF2 in particular (r=0.775). Coupling the steep relationship of relative SPARC expression with PD-BS (r=-0.753) the formula SPARC × 1/PREMEF2 gave an improved correlation (r=-0.893). Conclusion. A formula based on SPARC mRNA and PRAMEF2 methylation may be used to predict remaining BM-MSC longevity and related loss of multipotentiality independent of donor age.